Challenges of Home Tutors in Complying With Malaysian Tax Requirement - NAWAWI, NURNAZREENA; HAMID, NADIAH ABD; YUSOP, ROHAYU; GHAZALI, NORLAILA; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
Home Tuition has become a phenomenon in our country. Statistical reports have indicated an increasing number of tuition centres registered from 2010 to 2013 (MOE, 2013). This is because home tuition is convenient and time-saving since parents do not need to send their children to the tuition centre. According to the survey conducted by salary explorer (2020), in Malaysia, the average income for full-time home tuition is about RM8, 870 per month. This shows that the income received by home tutors is more than the minimum amount subjected to tax. However, the government faces difficulty in tracing their actual income since the majority of them did not declare it as the payment received in cash. From the IRBM report, for the year of assessment 2017, only 15.24% of the individual taxpayers complied in paying their income tax, and this percentage would also include home tutors. Specifically, this study examines the effect of factors such as knowledge, morale, and penalty on tax compliance of home tutors in Malaysia. The samples consist of home tutors registered under Private Tutor Company based in Kuala Lumpur and Selangor. This study employed a questionnaire survey for the data collection method and 167 respondents answered the questionnaires distributed online such as through WhatsApp and email. All of the data were recorded under an excel spreadsheet and analyzed using SPSS version 16. The result indicated that all of the factors have a significant relationship with tax compliance. This can be useful to the government in analysing the arising issue. The findings send an important signal to the government that more tax education programs should be carried out to transfer tax knowledge to the individual taxpayers. This is vital because by having sufficient tax knowledge, taxpayers will understand their responsibilities to comply with tax obligations.